1990
DOI: 10.1111/j.1399-3054.1990.tb05682.x
|View full text |Cite
|
Sign up to set email alerts
|

Indole‐3‐acetic acid uptake in isolated protoplasts of the moss Funaria hygrometrica

Abstract: Protoplasts of the moss Funaria hygrometrica Hedw were used to study the mechanism of Indole‐3‐acetic acid (IAA) accumulation. Three main components appeared to be involved. 1. The pH gradient between plasma and outer medium is the basis for an anion trap. The protonophores carbonylcyanide m‐chlorophenylhydrazone (CCCP) and carbonylcyanide p–trifluoromethoxyphenylhydrazone (FCCP) reduce IAA accumulation by destruction of the pH gradient. 2 An intact efflux carrier could be demonstrated by an increase of IAA ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Among basal land plants, e.g. the moss Funaria hygrometrica, TIBA inhibits IAA efflux from protonema and rhizoids and increases IAA accumulation in protoplasts (Geier et al, 1990). Therefore, we also measured cell division and cell elongation in the presence of 100 mM TIBA.…”
Section: Tiba Slightly Inhibits Cell Division and Suppresses Cell Elomentioning
confidence: 99%
“…Among basal land plants, e.g. the moss Funaria hygrometrica, TIBA inhibits IAA efflux from protonema and rhizoids and increases IAA accumulation in protoplasts (Geier et al, 1990). Therefore, we also measured cell division and cell elongation in the presence of 100 mM TIBA.…”
Section: Tiba Slightly Inhibits Cell Division and Suppresses Cell Elomentioning
confidence: 99%
“…Whereas some studies have reported that PAT inhibitors have effects on gametophyte development (Geier et al, 1990;Schwuchow et al, 2001), a recent study of five different mosses suggested that long-range PAT occurs in the subordinate sporophyte generation, but not in the gametophyte leafy shoot (Fujita et al, 2008). Consequently, it appears likely that tightly controlled local auxin biosynthesis is important in mosses, and that increased knowledge about these processes could shed light on the ancestral mechanisms for creation of auxin maxima in plants.…”
Section: Introductionmentioning
confidence: 99%